PERMAINAN BOLAVOLI MINI UNTUK ANAK SEKOLAH DASAR - Sri Mawarti (Jurnal Pendidikan Jasmani Indonesia, 2009)
The aim of this article is to give better understanding about mini volleybal game. This game can be played with a little or a lot of players in the elementary school. The distinguished of this game is on the existing regulations. The mini volley ball games for the elementary school do not use the standart rules, but the rules are simple. Enjoyment of the players becoming priority to achieve. The physical and mental aim conducted through the game and its suitable for elementary student to played. Keywords: Mini volleyball game, Elementary schools.